Total auxin level in the soil–plant system as a modulating factor for the efectiveness of PGPR inocula: a review (2023)
ABSTRACT: Biofertilizers are an alternative to face the sustainability problem that chemical fertilizers represent in agriculture. Among them, plant growth-promoting rhizobacteria (PGPR) is a microbial group with high potential, but lack of reproducible results from their application is a bottleneck for its use in agricultural production. Here we highlight a factor that could partially explain this inconsistency: the total auxin level in the soil–plant system. Auxin production is recognized as a main mechanism for plant growth promotion by PGPR; however, the final effect of auxins depends on a fine balance of its content, and this will be a result of all the sources of auxin compounds in the system. In addition to the auxins produced by inoculated bacteria, the plant itself produces its own hormones as part of complex physiological processes, varying in amount and sensitivity. Also, soil organic matter displays like auxin activity, causing plant responses just like those produced by added auxins. Therefore, the inoculation of an auxin-producing PGPR on plants might cause a wide variety of responses, ranging from effective growth promotion to growth restriction, depending on the total auxin content in root tissue. We think this must be considered for the practical use of bacterial biofertilizers, in order to have better and more consistent results of inoculation.